Evaluation of Running Speed and Distance Throwing After Doing Needle Intervention (Dry Needling) at Sriwijaya Sports Students Palembang: Evaluasi Kecepatan Lari dan Jarak Lempar Setelah Dilakukan Intervensi Tusuk Jarum (Dry Needling) pada Siswa Olahraga Sriwijaya Palembang - Septadina, Indri Seta; Suciati, Tri; Adnindya, Msy Rulan (Sriwijaya Journal of Medicine, 2018)
The factor supporting the achievement sports is physical skill consisting of speed, the power, agility, coordination and time reaction. Performance of speed determined by motion of the body as the arm and limbs that consisting of components such as muscle, bone, joints, vascularisation and innervation..Stimulation on nerve can improve the ability muscle then it can increasing the physical skill. The method often used is electric stimulator and dry needling. The purpose of this research is to assess running speed and throwing distance through intervention a dry needling to 35 students of Sriwijaya Sport High School Class XII with one group pretest and posttest design.The result showed average of running speed before dry needling is 7,48 ± 0,94 and after dry neddling is 7,44 ± 0,70. However statistical tests using the test paired t get p value = 0,679 (α =0,05 (p>α).The measurement result of throwing distance before dry neddling is 15,61 ± 8,54 and after dry needling is 16,35 ± 8,90. Wilcoxon test shows that p value = 0,077 (α =0,05 (p>α). The result showed that there is no difference between speed run and distance throwing before and after conducted a needle intervention dry ( dry needling ).